The Influence Of Influencer Credibility On Purchase Intention With Brand Trust As a Mediating Variable (Study on Somethinc Calm Down Moisturizer Cosmetic Products Labeled "Tasya Farasya Approved" in Bandar Lampung) - Elsa Dea Damayanti; Dorothy Rouly Haratua Pandjaitan; Nuzul Inas Nabila (International Journal of Economics, Business and Innovation Research, 2026)
This study is motivated by the increasing role of influencer marketing in the digital cosmetics industry, particularly the use of the “Tasya Farasya Approved” label on Somethinc Calm Down Moisturizer as a representation of influencer credibility in building brand trust. This research aims to analyze the effect of influencer credibility on purchase intention with brand trust as a mediating variable among consumers of Somethinc Calm Down Moisturizer in Bandar Lampung City. This study employs a quantitative approach using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method processed with SmartPLS, involving 204 respondents. The results indicate that influencer credibility has a positive and significant effect on brand trust and purchase intention, while brand trust also has a positive and significant effect on purchase intention. Furthermore, brand trust is proven to positively and significantly mediate the effect of influencer credibility on purchase intention, classified as complementary mediation (partial mediation). These findings confirm that influencer credibility plays a strategic role in enhancing consumer purchase intention through the development of brand trust.